Recessive transition of rural residential land use from the perspective of value co-creation: A case study of Yiwu City, Zhejiang - ZHANG Cong, LONG Hualou, FENG Dedong (Ziyuan Kexue)
[Objective] This study aims to reveal the the theoretical logic and implementation path of recessive rural residential land use transition from the perspective of value co-creation, providing references for promoting rural residential land redevelopment. [Methods] This study employed theoretical analysis and case study methods, based on relevant theories of value co-creation and land use transition, constructing a theoretical analysis framework for realizing recessive rural residential land use transition through value co-creation. The case of Yiwu City, Zhejiang Province, was used for illustration. [Results] (1) Value co-creation of ural residential land follows the process model of “value consensus-value execution-value win-win” and the operational paradigm of “subject interaction - capacity embedding - benefit sharing”, driving the “element integration - structure reorganization - function optimization” of rural residential land use system, resulting in the dynamic evolution of diverse values such as residential security, economic property, production and operation, ecological protection, and cultural inheritance, and achieving the recessive rural residential land use transition. (2) Yiwu’s practice path of guiding multiple stakeholders to interact collaboratively, constructing “value consensus” for rural residential land, driving with multiple forces, and implementing “value execution” for rural residential land through multi-dimensional rule interaction is a successful model for realizing the recessive rural residential land use transformation through value co-creation. (3) Through the practice of value co-creation, Yiwu has achieved a transformation of the functional value of rural residential land from residential security orientation to economic property orientation, and then to a comprehensive and coordinated approach that encompasses residential security, production and operation, economic assets, and ecological protection, etc. [Conclusion] Guiding recessive rural residential land use transformation through value co-creation is feasible. In the future, we should aim at the rural transformation needs and changes in stakeholder demands, identify the dominant subjects of value consensus, the core forces of value execution, and the key rules of value win-win, and promote recessive transition and redevelopment of rural residential land use according to local conditions, enhancing the scientific basis of decision-making.